The Role of Thinking Styles in Career Development Among Chinese College Students. Issue 3 (September 2017) - Li, Mengting; Fan, Weiqiao
Abstract : Thinking styles define individuals' marked preferences in how they learn about or process information. This study considered the function of collecting and processing information in career exploration and decision making, and examined thinking styles as a predictor of career decision‐making difficulties (CDMD) and career exploration as a mediator of this relationship. Chinese college students ( N = 463) responded to measures of thinking styles, career exploration, and CDMD. Results partially supported the contribution of thinking styles to career exploration and CDMD. Type I styles, characterized as more creativity‐generating, positively predicted career exploration and negatively predicted CDMD. Type II styles, characterized as more norm‐favoring, positively predicted CDMD. Partial mediation was supported in the link between Type I styles and lack of information through career environment exploration. The benefits of type styles should be highlighted for career guidance and counseling among Chinese college students and should be validated in different cultural contexts.